Penerapan SEO Dalam Strategi Pemasaran Perusahaan - Fiky Budi Dewanto; Muhammad Habib Purnama Febrian; Muhammad Raihan Amir; Ida Farida Adi Prawira (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This article aims to determine the influence of implementing SEO (Search Engine Optimization) in marketing company. In this article, data were collected using the SLR (Systematic Literature Review) method and analyzed qualitatively. Findings suggest that as time goes by, trading companies are starting to adapt by changing their conventional trading systems to modern systems, including their marketing strategies to reach wider and more target markets. A modern marketing strategy that combines digital media with marketing skills has become a new marketing technique called digital marketing. Digital marketing can be maximized by utilizing the internet as a marketing medium, one of which is by creating a website that markets the company's products or services. In order to compete with other websites, the website created must also be optimized for use, one of which is by implementing SEO. SEO optimizes a company's website so that it remains at the top of the first page of searches on search engines. In addition, implementing SEM (Search Engine Marketing) in the form of advertising on search engines, will have an impact on traffic from potential consumers and be able to increase sales of the products or services offered. Keywords: SEO; digital marketing; marketing strategy.